Galician-Catalan Lineages in Sardinia. The Masones-De Lima Soutomaior in the Defence of the Island during the War of the Spanish Succession - Pinna, Salvatore (Madrygal. Revista de Estudios Gallegos, 2023)
The article investigates the Sardinian branch of the Galician-Catalan Masones-De Lima-Sotomayor family and the role played by several of its members in the military and diplomatic fields, as well as in the defence of the island during the War of Spanish Succession. Thanks to unpublished data from the Diocesan Historical Archive of Nuoro and the National Historical Archive of Madrid, the complete genealogy of the family is reconstructed. On the one hand, it underlines the importance that the Sardinian town (then called villa) maintained at that time, thanks to its socio-economic conditions worthy of the larger towns. On the other hand, it is possible to describe the illustrious figures of this family, without the veil of indecision caused by the numerous homonyms. Finally, the study provides new threads of connection between Galicia and Sardinia, showing, in this way, the full belonging of the Sardinian island to the reality of the Hispanic monarchy with all its territories, beyond those that were part of the Crown of Aragon.
Keywords: Soutomaior; Masó; Sardeña; Núoro; War of the Spanish Succession